Reviving Ceremonial Literary Practices to Restore Spiritual Influence: The Abbasid Caliphate from (550-656 AH /1155-1258AD) - Alqadahat, Mohammad Abdullah; Abdelkareem , Abdel Nasir Yousuf (Al-Qanṭara, 2025)
dynasty, centralized its power by merging religious legitimacy with hereditary succession, claiming descent from the Prophet Muḥammad as a way of asserting divine legitimation. Central to this centralization of power was the tactical use of poetry as a state propaganda tool. While previous scholarship has addressed the Abbasid era's political and religious institutions, poetry's instrumental role in validating the caliphate's authority is yet to be exhaustively probed. In this study, the means whereby poetry was applied to shape people's opinions, legitimize the caliphs, and aid their divine right to rule is examined. Focused on the heights of Abbasid power—namely during the periods of Caliphs Al-Nasir and Al-Mustaḍīʾ—the research highlights how poets like Sibṭ Ibn al-Taʽāwīḏī produced state-sponsored poems that assisted in elevating the political and religious status of the caliphs. The poetic compositions were accorded front-stage positions in public festivities, religious ceremonies, and official discourse, transforming cultural performances into ideological instruments. From the records of the past, literary texts, and recent scholarship, including Hayrettin Yücesoy's Disenchanting the Caliphate, this study talks about how poetry functioned not just as creative expression but as a calculated way of establishing and legitimating Abbasdauthority. Through an exploration of the intersections of literature, religion, and politics, the study provides a clearer image of how the Abbasids managed to sustain their rule and shape the sociopolitical atmosphere of medieval Islamic society. The findings contribute to broader arguments regarding political communication, literary culture, and the role of ideology in pre-modern statecraft.